Assessment of Obesity and Serum Uric Acid in General Population - Sarpal, Vidya Sagar; Babbar, Jyoti Bhushan; Ranjan, Rajesh; Kishore, Manjari; Lata, Prasoon; Shukla, Kamlesh (Asian Journal of Medical Research, 2021)
Background: To assess obesity and serum uric acid in general population. Subjects and Methods: One hundred six adult subjects in age ranged 18- 58 years of either gender was selected. Height was measured with a standard stadiometer and weight was measured in light clothing on an electronic scale. Body mass index (BMI) was calculated by dividing the weight (kg) by the height (m) squared. Serum uric acid was measured by the PAP- uricase method. Results: The mean age of males was 34.5 years and in females was 38.2 years, weight was 67.8 Kgs and in females was 54.3 Kgs, height was 173.2 cm in males and 154.7 cm in females, BMI was 29.4 kg/m2 in males and 24.3 Kg/m2in females and uric acid was 372.4 ?mol/L in males and 286.2 ?mol/L in females. There were 6 underweight, 4 normal, 2 overweight and 7 obese males and 3 underweight, 3 normal, 2 overweight and 4 obese females having raised uric acid respectively (364.7-996.2?mol/L). A significant difference between UA and subjects with different BMI was observed (P< 0.05). Conclusion: It was found that serum uric acid was strongly associated with obesity. However, it was a small study, a large study is required to validate the findings.